Design of an affinity chromatography resin for purification of IgG - Núñez Gómez, Luis; Govantes, Fernando (Biosaia: Revista de los másteres de Biotecnología Sanitaria y Biotecnología Ambiental, Industrial y Alimentaria, 2013)
Several brands of affinity chromatography matrices based on protein A (Uniprot Q53779) of Staphylococcus aureus are available on the market for the purification of IgG. The use of the called Z domain represents an improvement relative to the B domain of protein A itself used in these matrices, and is responsible for capturing the IgG (Hober et al., 2007, Cedergren et al., 1993). We have performed modifications to optimize the IgG capture domain in conjunction with an inert chromatography matrix. To this end, we designed our own resin to achieve good IgG purification capacity at a moderate cost. For the choice of commercial matrix were considered a number of parameters, such as the need to use a crosslinker agent, type of bond it can form, amount of protein it can bind, pH range in which it is stable, its compatibility with buffers and its cost. Our work demonstrated that the inert matrix Sulfolink ™ (ThermoScientific ®) was the most suitable and efficient. In addition, this matrix did not require a crosslinker agent to join our protein A. By using this experimental design, we were able to achieve a performance of 18.56 mg binding capacity IgG / ml resin. Sophia Hober, Karin Nord, Martin Linhult. Protein A chromatography for antibody purification. Journal of Chromatography B, 848 (2007) 40–47. Lena Cedergren, Roland Andersson, BirgerJansson,Mathias Uhlén and Björn Nilsson.Mutational analysis of the interaction between staphylococcal protein A and human IgG1. Protein Engineering vol.6 nº4, 441-448 (1993).